2021
DOI: 10.3390/jcm10215177
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Mesothelioma Nodal Status: Where Are We at?

Abstract: Due to the lack of both prospective trial and high-volume retrospective studies, the management of clinical N+ malignant pleural mesothelioma (MPM) patients remains highly debated. Node positive patients show poor survival compared with node-negative ones; thus, lymph node staging appears crucial in determining treatment strategy. Notwithstanding the improvement in pre-treatment staging and the update on lymph node classification in the 8th edition of TNM, several open controversies remain on N parameter. How … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…A previous study also reported that the prognosis of epithelioid patients with MPM was the best among the 3 subtypes ( 52 ). Positive lymph node status, except that in N2, was also significantly associated with prognosis, and we found that the proportion of patients with MPM lymph node metastasis was nearly 35%, which was roughly the same as that previously reported ( 53 ). However, it remains unclear whether the location and number of lymph nodes are also principal prognostic factors, and further research is needed in this area.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study also reported that the prognosis of epithelioid patients with MPM was the best among the 3 subtypes ( 52 ). Positive lymph node status, except that in N2, was also significantly associated with prognosis, and we found that the proportion of patients with MPM lymph node metastasis was nearly 35%, which was roughly the same as that previously reported ( 53 ). However, it remains unclear whether the location and number of lymph nodes are also principal prognostic factors, and further research is needed in this area.…”
Section: Discussionsupporting
confidence: 90%